Experimental parametric analysis of an energy harvester based on highly nonlinear solitary waves. (April 2017) - Li, Kaiyuan; Rizzo, Piervincenzo
We investigate experimentally five different designs of an energy harvester based on mechanical vibration and highly nonlinear solitary waves. The harvester consists of a metamaterial formed by granular chains, an oscillator that taps the metamaterial, a solid in contact with the metamaterial, and a piezoelectric element glued to the solid. The overall principle is that the oscillator taps the metamaterial and creates a train of solitary waves along each chain. At the interface between the chains and the solid, part of the acoustic energy refracts into the solid where it coalesces at a point and triggers the vibration of the solid. Here, a transducer converts the focalized stress wave and the waves generated by the reverberation with the edges into electric potential. In the study presented in this article, we evaluate the effect of certain harvester parameters on the amount of energy that can be extracted. We considered five different designs by changing the oscillator, the dimension of the array, the solid material, and the transducer boundary condition. For each design we computed the power density, and we found that the density obtained with the best design is four orders of magnitude higher than the worst design.